MODERN CONDITION OF THE ACTIVITY OF THE CREDIT UNIONS UKRAINE - Тымоць, Мирослава (SWorldJournal, 2022)
Modern condition of the activity of the credit unions on the financial market of Ukraine is analyzed in the article. It is considered the influence of a state regulator on the dynamics of the non-banking financially – credit institutions, it is installed